Faktor-Faktor yang Memengaruhi Revisit Intentiondi Daya Tarik Wisata Waduk Malahayu - Anam, Muhammad Syariful; Yulianti, Wina; Fitrialoka, Tania; Rosia, Rina (JURNAL DESTINASI PARIWISATA, 2021)
This study aims to identify whether the image of the destination, tourist facilities, accessibility, and word of mouth affect the revisit intention of tourists to the Malahayu Reservoir Tourist Attraction. The sample used in this study amounted to 100 people who were taken using purposive sampling technique. Meanwhile, multiple linear regression was used to analyze the data that had been collected. The results obtained from data analysis, namely simultaneously the destination image, facilities, accessibility, and word of mouth variables have a significant effect on revisit intention. Partially, the image of the destination has a positive but not significant effect on revisit intention. Meanwhile, the accessibility variable does not partially affect revisit intention. However, the facilities and word of mouth variables partially have a positive and significant effect on the revisit intention of tourists to the Malahayu Reservoir Tourist Attraction. From the results of this study, provide recommendations to local governments and tourism managers to improve the quality of facilities in tourist areas and improve access road conditions to tourist attractions that have been damaged. In addition, to improve the image of the destination, it can be done by developing regional cultural activities and attractions in tourist areas. Including improving governance, infrastructure, and cleanliness of tourist attractions as an effort to develop the Malahayu Reservoir destination. Keywords: Accessibility, Destination Image, Facilities, Revisit Intention, Word of Mouth